Dimensions of Poetic Expression in Drama and Theatre - Gudavičiūtė, Aušra (Colloquia, 2016)
The author of this article has two goals: a theoretical one – to use the concepts of “poetic drama” and “poetic theatre,” which date from the first half of the twentieth century, to explore the concept of “poetics in theatre,” and a practical one – to discuss poetic forms of expression in contemporary theatre. The author reveals that the concepts of “poetic drama” and “poetic theatre” still lack strict genre definitions, so that poetic means of expression in drama and theatre can only be named. She discusses means of poetic expression within several examples of contemporary Lithuanian theatre – the plays “Audra” (The Tempest, by William Shakespeare; staged in 1997); “Jobo knyga” (The Book of Job, from the Old Testament; staged in 2014); Nutolę toliai (Distant Distances, based on the poetry of Petras Širvys; staged in 2010); and the performance “Gondii sindromas” (The Gondii Syndrome, by Gabrielė Labanauskaitė; 2014) – and comes to the conclusion that poeticism is expressed both through the reinforcement of early twentieth century principles about the use of poeticism in drama and their deconstruction, and in the highlighting of characteristics typical of postdramatic theatre – the shifting of emphasis from meaning generated by spoken discourse to sensuality, spatialisation, “textual landscape,” dedramatizing, and so on. Even though postdramatic theatre deconstructs traditional means of expressing poeticism – the generating of a poetic verbal text through drama – the author discerns, in postdramatic theatre, continuation of neoromantic Lithuanian drama traditions.